Eggert Petersen, Knud-Erik Sabroe, Ole Steen Kristensen & Bo Sommerlund, Danskernes tilværelse under krisen, Århus: Aarhus Universitetsforlag, 1987, 383 s. (2 bind), kr. 140,00. - Bryder, Tom (Politica, 1988)
-